Caregivers' experiences with the diagnosis of hearing loss - Hagedorn, Elfriede (Division of Communication Sciences and Disorders, 2015)
Knowledge of the impact of a diagnosis of hearing loss in children on their caregivers and the nature of their relationships with professionals during this process is inadequate in South Africa. The purpose of this study was to understand the experiences and perceptions of caregivers of diagnosis of hearing loss in their children. A qualitative, retrospective, narrative inquiry research design was used. Participants who were purposefully selected included one couple and 12 caregivers in the Tshwane Metropolitan area. They were interviewed using an in-depth interview method. The narrative data was subjected to in-depth thematic analysis. Three themes emerged from the data: 1) The catastrophic emotional impact of diagnosis, 2) The good and the bad of professional interaction, 3) Imbalanced relationships, strained resources and resulting identity threats. The discussion focused on the deeply emotional nature of the participants' experiences and the changes that ensued during and following the diagnosis of hearing loss in their relationship with their child and the wider community and how this impacted on their sense of identity. The study concluded that diagnosis has extensive, pervasive and disruptive effects on caregivers and that the professional plays an important role in shaping that experience. It thus makes recommendations for a humanistic, family-centred, paediatric audiology practice.